A new species of Suezichthys (Teleostei: Perciformes: Labridae) from the south-eastern Pacific, with a redefinition of the genus and a key to species - Russell, Barry C.; Westneat, Mark W. (Zootaxa, 2013)
A new species of the fish family Labridae, Suezichthys rosenblatti, is described from specimens collected at Isla San Felix, Isla Juan Fernandez and Isla San Ambrosio, off the coast of Chile. Suezichthys rosenblatti is distinct in having a combi-nation of 11 dorsal fin soft rays and 11 anal fin soft rays. It falls in the group of species that has 1½ scale rows above the lateral line and lack a scaly sheath at the base of the dorsal and anal fins (S. aylingi Russell, S. caudovittatus Russell, S. gracilis (Steindachner & Döderlein) and S. soelae Russell). Unlike other members of this group, S. rosenblatti has haemal arches on vertebrae 10–11 (versus haemal arch only on vertebra 10). The monotypic Nelabrichthys ornatus (Carmichael) is now included in the genus Suezichthys and a revised generic description and key to species of Suezichthys is provided. The occurrence of S. rosenblatti in the south-eastern Pacific and S. ornatus in the south-western Indian Ocean and south Atlantic Ocean represent major range extensions of the genus Suezichthys.